In Silico Study: Prediction the Potential of Caffeic Acid As ACE inhibitor - Bare, Yohanes; Kuki, Agustina Dua; Daeng Tiring, Sri Sulistyaningsih Natalia; Rophi, Apriani Herni; Krisnamurti, Gabriella Candrakirana; Tirto Sari, Dewi Ratih (El-Hayah : Jurnal Biologi, 2019)
Hypertension is an abnormal increase in blood pressure. Regulating blood and cardiovascular function have correlated with the ACE pathway. To decrease blood pressure can use the ACE inhibitor. This paper aims to predict potential of Caffeic Acid as anti-hypertension by blocking the ACE pathway. The method in this research used in silico study. The protein was obtained from Protein Data Bank (PDB) and the ligand was obtained from PubChem. Molecular docking was performed by using HEX and visualization analysis was analyzed by using Discovery Studio. The interaction of caffeic acid and ACE has a functional as anti-hypertension roles. The evidence by twelve amino acid, which bind with the caffeic acid (ASP377, ASN277, ASN285, GLU376, ALA170, ASN167, ASN374, THR372, THR166, CYS370, GLU162 and PRO163). The chemistry bond was formed are hydrogen bond, van der Waals and electrostatics in amino residue ASP377. This binding could stop the synthesis of AT-I to AT-II which pathway to hypertension. Caffeic acid has a potential role as anti-hypertension by inhibiting ACE.